Effect of white garlic powder (Allium sativum) on in vitro ruminal fermentation - Sahli F.; Moujahed N.; Darej C.; Guizani O. (The value chains of Mediterranean sheep and goat products. Organisation of the industry, marketing strategies, feeding and production systems, 2016)
The current study aimed to evaluate the effects of increasing doses (0, 4, 8, 16, 32 and 64 mg/50 ml of buffered rumen fluid from sheep) of garlic powder (GP) on in vitro fermentation characteristics. Doses of garlic powder were added to 500 mg of a diet composed of 50% of rye-grass hay and 50% of concentrate on dry matter (DM) basis. The medium of incubation consisted on ruminal liquid extracted from sheep, mixed in equal proportions with a buffer solution and introduced in 100 ml glass syringes (39°C). For each garlic dose and incubation, 2 syringes were reserved for sampling liquid to determine pH and ammonia nitrogen (NH3-N) and 3 for true organic matter degradability (TOMD) measurements (5 syringes in total). Two successive 24 hincubations were practiced and at the end of each gas production was measured. Partitioning factor (PF) was estimated as the ratio between TOMD and the gas produced at 24 h of incubation. Microbial biomass (MBM) was estimated on the bases of truly degraded substrate and PF. Results showed that GP had no effect on gas production for doses 4, 8 and 16 mg compared with control. However, when 32 and 64 mg of GP were added, gas production increased (P<0.001) by about 13% for each dose. An increase (P<0.0001) in NH3-N concentration was recorded with 4 mg and 8 mg of GP compared with control, Whereas adding 16 mg of GP resulted in a NH3-N concentration equivalent to control. The doses of 32 and 64 mg of GP diminished the NH3-N concentration by 20 % compared with control. Truly organic matter degradability was similar (72.2 % on average) for all doses except 64 mg of GP, where a slight but significant (P<0.001) increase was found (77.7%). Garlic powder did not affect PF values when adding 4, 8, 16 or 32 mg of GP compared with control. However, the dose of 64 mg increased significantly (P<0.0001) the PF value. Microbial biomass values obtained with doses 4, 8, 16 and 32 mg were equivalent to those obtained from control, while the value observed with 64 mg was significantly (P<0.001) higher. It was concluded that GP could induce changes in rumen fermentation as measured in vitro. Some of these modifications could have positive effect on feeding efficacy in ruminants. Further measurements are needed to investigate mainly the effect of garlic on microbial activities, such as effects on volatile fatty acid (VFA) production and composition and on animal performances.
Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2015/06/16-18, Montpellier (France)